2021
DOI: 10.1186/s40104-020-00526-2
|View full text |Cite
|
Sign up to set email alerts
|

Progress in ileal endogenous amino acid flow research in poultry

Abstract: The progress in our understanding of the endogenous protein concept over the past century is reviewed. Non-dietary proteins found in the digesta at the terminal ileum of poultry, known as endogenous protein loss, are comprised of digestive secretions, mucus and sloughed gut epithelial cells. The measurement of this loss is of fundamental importance because it is an indicator of gut metabolism and is essential to adjust apparent estimates of ileal amino acid digestibility. The ileal endogenous amino acid losses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 89 publications
3
28
2
Order By: Relevance
“…The concentrations of EAA in the ileal digesta are within the range reported in the literature ( Ravindran, 2021 ). The higher proportions of Glu, Asp, Thr, and Ser determined in the endogenous protein were as expected.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The concentrations of EAA in the ileal digesta are within the range reported in the literature ( Ravindran, 2021 ). The higher proportions of Glu, Asp, Thr, and Ser determined in the endogenous protein were as expected.…”
Section: Discussionsupporting
confidence: 85%
“…The EAA values determined at the ileum therefore relate to the algebraic differences between that secreted and absorbed ( Moughan, 2003 ; Ravindran et al, 2004 ). The source of endogenous proteins and the entry point into the GIT further complicate this dynamic ( Ravindran, 2021 ). When digestive enzymes dominate the endogenous flow, the proteins pass through the duodenum and jejunum where there is greater opportunity for digestion and absorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, serum IGF-1 concentration is in uenced by nutritional status, particularly protein-energy malnutrition. It has been reported that serum IGF-1 concentration is reduced in models of severe energy restriction or protein restriction in young growing rats 15 . In this study, the serum IGF-1 concentration in four NFD groups decreased by varying degrees which could re ect some protein restriction.…”
Section: Discussionmentioning
confidence: 99%